A randomized trial on the acute and steady-state effects of a new antidepressant, vortioxetine (Lu AA21004), on actual driving and cognition - Theunissen, E L; Street, D; Højer, A-M; Vermeeren, A; van Oers, A; Ramaekers, J G (Clinical pharmacology and therapeutics, 2013)
The aim of this study was to assess the effects of a novel antidepressant, vortioxetine 10 mg, on driving, cognitive, and psychomotor performance in 24 healthy subjects in a double-blind, placebo-controlled, three-way crossover design. Mirtazapine 30 mg was included as an active comparator. Drugs were administered in the evening of 15 consecutive days. Performance was measured in the morning of days 2 and 16, using standardized tests measuring on-the-road driving, memory, tracking, divided attention, and vigilance. The statistical analysis on the primary measure of driving, i.e., SD of lateral position showed noninferiority of vortioxetine on days 2 and 16, and inferiority for mirtazapine on day 2. Vortioxetine did not cause cognitive or psychomotor impairment. Mirtazapine, however, impaired cognitive and psychomotor performance on day 2. Most of these effects disappeared after multiple doses of mirtazapine. To conclude, vortioxetine did not impair driving, cognitive, or psychomotor performance after single or multiple doses.